Localization of a speaker in a room by using microphone Arrays - Muhammad Afaque Khan (2018)
In this thesis a Source Localization DSP program implemented on D.M.C6713 is analyzed and ported to D.M.C6657. The DSP program on D.M.C6657 is ex-tended to take advantage of the better specifications of the new hardware. A Source Localization progam is also developed in MATLAB that uses Multi-channel Cross Correlation Coefficient (MCCC) algorithm for SDOA estimation.